Sensitive and rapid models of PCR-based methodologies for admixture detection and quantification of domestic meats - Hanapi, Ummi Kalthum (2016)
This research project was undertaken to develop cost-effective, fast and sensitive PCRbased methods for fraud identification of meat-based products. Meats and meat-based product samples included in the analyses were pig, ruminant, avian and rabbit. Two methods were established for qualitative and quantitative evaluation of animal group contamination/ admixture in meat-based products. In this study, NADH-dehyrogenase subunit 4 (Nad 4) gene of mitochondrial was used. Nad 4 gene holds great potential for identifying meat type due to high interspecies variability of the gene sequence. To date, very little attention was given in meat identification using Nad 4 gene. To further recognize the potentially important of Nad 4 gene, the sequence variability has been explored in identifying differences in the designated meat types. For qualitative analysis, a common primer multiplex PCR (CP-M-PCR) was developed by using a common forward primer, species-specific adapter reverse primers and a common adapter reverse primer.The designed primers were analyzed in silico and tested against pure meat DNAs. The primers successfully generated specific fragments of 267, 370, 504, and 548 bp lengths for pig, ruminant, avian and rabbit meats, respectively. A serial dilution of each reverse primer was used to determine and compare the sensitivity of CP-M-PCR to conventional multiplex PCR system. The detection limit of CP-M-PCR was evaluated with 10-fold serial dilutions of DNA concentration. The use of adapter sequence at the 5’-end of the species-specific reverse primers was shown to increase the efficiency of the PCR amplification and the application of a single forward primer reduced the complexity in multiplex PCR system. Bands of specific amplification can be detected from the PCR assays containing as low as 10-6 μM of adapter reverse primer. The CP-M-PCR limit of detection was as low as 0.01 ng of DNA for the four groups of meat which was deemed to be sufficient to qualitatively detecting accidental or intended contamination in meat products. The developed system was applied to 42 commercial meat-products and showed the presence of avian meat in analyzed ruminant (3/14), rabbit (2/2) and pig (1/11) samples. In the subsequent work, a quantitative competitive PCR (QC-PCR) was developed to determine the percentage of contamination. Based on the CP-M-PCR results, six avian contaminated commercial meat-based products were quantitatively analysed using the calibrated QC-PCR. Prior to quantitative analysis, a competitor DNA of each animal meat group was constructed via site directed-mutagenesis processes. Site directedmutagenesis was used to introduce a 40 bp fragment comprising a 30 bp insert and 10 bp repeated sequence. The constructed DNA competitors were coamplified with the target DNA at different ratios of concentration and results were analyzed using UVIgeltec imaging software version 12.1. The results of QC-PCR showed that the percentage of contamination was in the range of 0.27 to 5.08% in the collected samples. The developed methods in this study are considered practical and valid alternatives in the context of a routine diagnostic laboratory where they are costeffective, efficient, and sensitive enough for qualitative and quantitative investigation of contamination or adulteration in meat products. The developed approaches are costeffective because theydo not require expensive equipment, consumable and reagent, and high level of technical expertise to perform the analyses. Thus, the models may serve as templates for any screening system such typing of transgenic organisms, analyzing of forensic materials, detection of pathogens to cancer research, studying metagenomics, analyzing gene expression and monitoring environment.